Canonical and Non-Canonical Aspects of JAK–STAT Signaling: Lessons from Interferons for Cytokine Responses - Majoros, Andrea; Platanitis, Ekaterini; Kernbauer-Hölzl, Elisabeth; Rosebrock, Felix; Müller, Mathias; Decker, Thomas (Frontiers in Immunology, 2017)
JAK-STAT signal transduction mediates cytokine responses. Canonical signaling is based on STAT tyrosine phosphorylation by activated JAKs. Downstream of interferon (IFN) receptors, activated JAKs cause the formation of the transcription factors ISGF3, a heterotrimer of STAT1, STAT2 and IRF9 subunits, and GAF, a STAT1 homodimer. In recent years several deviations from this paradigm were reported. These include kinase-independent JAK functions as well as extra- and intranuclear activities of U-STATs without phosphotyrosines. Additionally, transcriptional control by STAT complexes resembling neither GAF nor ISGF3 contribute to transcriptome changes in IFN-treated cells. Our review summarizes the contribution of noncanonical JAK-STAT signaling to the innate antimicrobial immunity imparted by IFN. Moreover, we touch upon functions of IFN pathway proteins beyond the IFN response. These include metabolic functions of IRF9 as well as the regulation of NK cell activity by kinase-dead TYK2 and different phosphorylation isoforms of STAT1.